(untitled) (ҚазҰУ хабаршысы. Экология сериясы, 2025)
Most of the pollutants from the atmosphere of the urbanised area get into the soil. Due to the increase in population and motor transport in Almaty city there is a high level of atmospheric air pollution, increased content of heavy metals in the soil. Accumulation of heavy metals by green trees from the soil positively affects soil conditions, in this regard, it is relevant to assess the current state of soil cover of regions where Thuja occidentalis L. and Platycladus orientalis L. trees grow. In the article, to determine the influence of western and eastern thuja trees on soil composition, soil were obtained with coordinates at point 2 and control point, where trees of thuja species grew side by side. Total and mobile content of heavy metals in soil (Cu, Zn, Mn, Fe) were determined by atomic absorption spectrometry. Morphological characterisation of the soil cover was made, granulometric composition and soil types were determined by the Tyurin method. Point 1 Thuja occidentalis L. humus content in soil cuttings on which the tree was growing showed maximum content of 3.82% in 0-10 cm, while Platycladus orientalis L. when growing the humus content is low 1.86%, the soil in point 2 opposite Platycladus orientalis L. humus content of 2.96% when growing Thuja occidentalis L. (2.14%) has a higher humus content compared to the augmented soil. Thuja occidentalis L. and Platycladus orientalis L. in the control, where the species grew together, the humus content is 3.1%. the pH value ranged from 8.26 to 8.81, with soil cuttings generally showing a strong alkaline environment. Among the heavy metals, Zn, Cu and Fe were found to be significantly above the MAC in the soil, meaning that the soils of the study area were contaminated with heavy metals. At profile 1, the soil on which western thuja grew has less amount of Zn, Cu, Mn, Fe compared to the soil on which eastern thuja grew, Mn- and others are above MAC. At profile 3, only the Fe size of Platycladus orientalis L. is higher in the overgrown soil. Thuja occidentalis L. and Platycladus orientalis L. where the species grew together, the amount of Mn decreased by 452.2µg/kg. The study showed that the accumulation of heavy metals in the soil decreased when growing the western thuja species compared to the eastern thuja species. Keywords: Thuja, soil cover, granulometric composition, humus, heavy metals, MPC